"Am I doing this all wrong?" Challenges and Opportunities in Family Information Management - Sannon, Shruti; Vorvoreanu, Mihaela; Fourney, Adam; Walker, Kathleen (Computer Supported Cooperative Work (CSCW), 2020)
Running a household requires a large amount of labor, from ensuring multiple bills are paid to organizing important documents. Failure to manage such information can have critical consequences for the financial and psychological well-being of the family; however, little is known about how families manage the full scale of information in the home. We introduce family information management (FIM) as a set of overarching practices involved in managing and coordinating household-related information. To understand how families engage in FIM, we conducted in-depth interviews with members of ten families, which included guided tours of their information archives. We found that families struggle to organize, store, retrieve, and share information, and that there are significant socioemotional costs to this work. We propose opportunities for designing technologies to support FIM and argue that, given the numerous challenges and unmet needs, the understudied area of FIM deserves further investment of research and design efforts.